Development of a Magnetic Loop Antenna for the Detection of Jovian Radiowaves at 20.1 MHz - Galvis Rodríguez, Hamilton David; Quintero Salazar, Edwin Andrés; Cardona Torres, Luisa Fernanda (TECCIENCIA, 2016)
Radio waves coming from the planet Jupiter are electromagnetic phenomena generated by synchrotron emission mechanism, due to the interaction of Jovian magnetic field with charged particles produced by the satellite Io. These radio waves fall directly upon the ionosphere affecting earth’s radio communications. At the Astronomical Observatory of the University of Technology of Pereira (OAUTP) the research group in Astro-engineering Alfa Orion, developed a magnetic loop antenna designed to resonate at 20.1 MHz, which coupled with the receptor and the software from NASA’s Radio Jove project enabled the observation of radio sources A, B, C, IoA, IoB and IoC from Jupiter, allowing the construction of a database for the study of the Jovian activity in radio waves.